THE ROLE OF INCLUSIVE EDUCATION APPROACHES IN MODERN DEFECTOLOGY (International journal of artificial intelligence, 2025)
This article explores the role of inclusive education approaches in modern defectology, focusing on how contemporary pedagogical practices support the learning and development of children with special educational needs. The article outlines key principles of inclusion, current models used in schools, and the evolving role of defectologists as facilitators of inclusive practices. The integration of students with physical, cognitive, and emotional disabilities into mainstream classrooms has transformed the responsibilities of special educators. Inclusive education, as a philosophy and practice, promotes equality, participation, and the personalization of learning, helping to build more tolerant and diverse educational communities